Innovative technologies and inclusion: Pathways to curriculum adaptation (Research, Society and Development, 2025)
Innovative technologies have played a fundamental role in promoting educational inclusion, offering new possibilities for adapting the curriculum to the needs of all students. This study aims to highlight practices, tools, and methodologies that favor the inclusion, autonomy, and meaningful learning of students who are the target audience of Special Education, converging the themes of technological innovation and school inclusion. These instruments favor the flexibility of content, methodologies, and assessments, enabling the curriculum to become more accessible without losing its pedagogical intent. A non-systematic, qualitative, and narrative literature review was conducted. Furthermore, artificial intelligence and adaptive learning systems have the potential to offer personalized learning paths, adjusting the pace and level of activities to the progress of each student. Another relevant aspect is the role of the teacher. Continuing education in educational technologies and inclusion is essential for teachers to know how to select, adapt, and integrate digital tools critically and meaningfully. Pedagogical mediation, combined with the conscious use of technology, contributes to a more equitable curriculum. Finally, the integration of innovative technologies into inclusive education should not be seen merely as technical support, but as a movement of pedagogical transformation. By promoting accessibility, autonomy, and participation, technology strengthens the construction of practices aligned with the principles of inclusive education and broadens the paths to a curriculum truly adapted to the needs of all.